2023
DOI: 10.1002/ecm.1588
|View full text |Cite
|
Sign up to set email alerts
|

Rarefaction and extrapolation with beta diversity under a framework of Hill numbers: The iNEXT.beta3D standardization

Abstract: Based on sampling data, we propose a rigorous standardization method to measure and compare beta diversity across datasets. Here beta diversity, which quantifies the extent of among‐assemblage differentiation, relies on Whittaker's original multiplicative decomposition scheme, but we use Hill numbers for any diversity order q ≥ 0. Richness‐based beta diversity (q = 0) quantifies the extent of species identity shift, whereas abundance‐based (q > 0) beta diversity also quantifies the extent of difference amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 86 publications
0
17
0
Order By: Relevance
“…Generally, β-diversity measures fall into two classes: direct calculation of the ratio between regional (γ) and local (α) diversity, and multivariate measures based on pairwise dissimilarities (Anderson et al 2011). Our ESS-based β-diversity estimate fundamentally differs from the recently developed beta diversity rarefaction and extrapolation methods in the package (Chao et al 2023), as well as from the sample coverage-based rarefaction β-diversity proposed by Engel et al (2021). Both approaches estimate β-diversity based on the ratio between estimated γ- to α-diversity, providing an average (regional) measure of β-diversity across all communities.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Generally, β-diversity measures fall into two classes: direct calculation of the ratio between regional (γ) and local (α) diversity, and multivariate measures based on pairwise dissimilarities (Anderson et al 2011). Our ESS-based β-diversity estimate fundamentally differs from the recently developed beta diversity rarefaction and extrapolation methods in the package (Chao et al 2023), as well as from the sample coverage-based rarefaction β-diversity proposed by Engel et al (2021). Both approaches estimate β-diversity based on the ratio between estimated γ- to α-diversity, providing an average (regional) measure of β-diversity across all communities.…”
Section: Discussionmentioning
confidence: 98%
“…In summary, the package proves valuable for ecologists working on α- and β-diversity, especially when dealing with incomplete and inconsistent sample sizes, which is a prevalent characteristic in samples of ecological communities, but particularly in samples of highly mobile and species-rich taxa. Additionally, it provides visual estimations for species richness and the number of shared species between two communities based on individual samples, offering a complementary approach to non-parametric methods, such as the Chao series of estimators (Chao 1984, Chao et al 2000, Chao et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicated burnt areas which were less urban, showed greater diversity estimates post‐fire than unburnt areas; thus, this bias was either negligible or outweighed by environmental (e.g., fire) drivers (Appendix S4). We also examined whether shifts in diversity estimates more likely reflected species richness or species abundance distribution shifts by estimating beta diversity within the iNEXT framework (Chao et al, 2023; see Appendix S4). Estimates were derived from comparisons of pairs of assemblages (see Appendix S4).…”
Section: Discussionmentioning
confidence: 99%
“…Estimating species richness has been a longstanding issue (Fisher et al 1943, Gwinn et al 2015 and many statistical methods exist to estimate true richness from observed species counts. For instance, the Chao family of non-parametric estimators, including the iNEXT (Hsieh et al 2016) and iNEXT.3D programmes (Chao et al 2021), are widely used to estimate asymptotic species richness based on rarefaction and/or the frequency of rare species within a sample (e.g., Mendenhall et al 2014, Palmeirim et al 2021, and have also been expanded to estimate detection-corrected β-diversity indices (Chao et al 2023). While addressing imperfect detection, the Chao/iNEXT estimators do not consider the influence of covariates on species occurrence or detection (McKenzie 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we use simulations to explore the impacts of imperfect detection on typical field study designs for SAR and β-diversity estimation, and assess the comparative performance of an abundance-based Chao estimator (iNEXT.3D/iNEXT.beta3D; Chao et al 2021Chao et al , 2023 and MSOMs to 1) estimate Species-Area Relationships (patch-level richness, SAR c-andz-values), and 2) model the relationship between covariates and pairwise β-diversity (pairwise Sørensen similarity, model slopes and intercepts). We test the sensitivity of estimators to variation in species detectabilities, and the sampling design used to assess communities.…”
Section: Introductionmentioning
confidence: 99%